The evaluation of right and left ventricular functions in children with episodic wheezing exposed to environmental tobacco smoke - Doksöz, Önder; Nacaroğlu, Hikmet Tekin; Ceylan, Gökhan; Çeleğen, Mehmet; Aşık-Nacaroğlu, Şenay; Can, Demet; Meşe, Timur; Ünal, Nurettin (The Turkish Journal of Pediatrics, 2017)
The objective of this study is to examine the right and left ventricular functions in children with episodic wheezing at the ages of 1-3 exposed to environmental tobacco smoke (ETS). Thirty-two children monitored at the Pediatric Allergy and Immunology Department of a Research and Training Hospital with the diagnosis of episodic wheezing were included. The prospective assessment of the patients was performed between May 2013 and February 2014. Twenty-five children with episodic wheezing not exposed to ETS formed the control group. The two groups were compared by conducting transthoracic two-dimensional and tissue Doppler echocardiography (TDE) examination in all of the cases. The average age of the study group (24 boys, 8 girls) was 33.1 ± 8.8 months, the average age of the control group (18 boys, 7 girls) was 31.9 ± 11.9 months. There was no statistically significant difference between the two groups in terms of age, gender, weight, height, and body mass index values. There was no statistically significant difference between the two groups for the right and left ventricular systolic and diastolic functions in the conventional echocardiographic measurements, and for the measurements of TDE. Limited number of patients is a major limitation of the study. These results should be supported by more comprehensive studies.
Keywords: children; ventricular functions; wheezing